Strategi Politik Hizbut Tahrir dalam Menegakkan Khilafah Islam di Indonesia - Edi Sabara Manik; Hasanuddin Hasanuddin (AL-FIKRA, 2018)
Hizb ut-Tahrir Indonesia (HTI) is an Islamic organization that became famous and became the subject of discussion after being dissolved by the Indonesian government through PERPPU no. 2 Year 2017. Many different views on the struggle Hizbut Tahrir Indonesia. The Indonesian government considers that the activities and ideas undertaken by HTI can divide the Unitary Republic of Indonesia (NKRI). However, some national figures assume that HTI's struggle is not contradictory to the constitution and the idea conveyed by HTI namely the Khilafah is part of the teachings of Islam. In this paper, the author examines how HTI embodies the idea of the Khilafah. From the results of the study can be concluded that there are three strategies undertaken in realizing the Khilafah is first, the stage of coaching and cadre (tatsqif); second, interaction and struggle (marhalah tafaul wal kifah); third, the Acceptance of Power and Application of Law by the State (Marhalah tathbiq ahkamul Islam).